Lipid removal in deuterium metabolic imaging (DMI) using spatial prior knowledge - de Graaf, Robin A.; Liu, Yanning; Corbin, Zachary A.; De Feyter, Henk M. (Magnetic Resonance : (Göttingen), 2024)
Deuterium metabolic imaging (DMI) is a novel method to generate spatial maps depicting dynamic metabolism of deuterated substrates, such as [6,6′-2H2]-glucose, and their metabolic products, like 2H-lactate. While DMI acquisition methods are simple and robust, DMI processing still requires expert user interaction, e.g., in the removal of extracranial natural abundance 2H lipid signals that interfere with metabolism-linked 2H-lactate formation. Here we pursue the use of MRI-based spatial prior knowledge on brain and non-brain/skull locations to provide robust and objective lipid removal. Magnetic field heterogeneity was accounted for using DMI-derived surrogate B0 and B1 maps, as well as through subdivision of the skull region into smaller compartments. Adequate lipid removal with an average suppression of 90.5 ± 11.4 % is achieved on human brain in vivo without perturbation of the metabolic profile in brain voxels, thereby allowing for the generation of distinct and reliable metabolic maps for patients with brain tumors.